1997
DOI: 10.1017/s003118209600875x
|View full text |Cite
|
Sign up to set email alerts
|

Dactylogyrus (Monogenea) infections on the gills of roach (Rutilus rutilus L.) experimentally exposed to pulp and paper mill effluent

Abstract: Experimental exposure to bleached kraft pulp and paper mill effluent (BKME) at a concentration of 10% significantly reduced the abundance and mean number of species of Dactylogyrus on the gills of naturally infected roach, Rutilus rutilus, over a 3 week period. Seven Dactylogyrus species were recorded which differed widely in their susceptibility to the effluent. The experiment coincided with a natural spring peak in dactylogyrid infections on roach. BMKE exposure did not prevent parasite reproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 6 publications
2
12
0
3
Order By: Relevance
“…It was observed in the present study that the prevalence and mean abundance of total monogeneans and A. mizelli were significantly greater in the lentic stretch. This significant difference corroborates previous studies that reported the use of monogeneans as indicators of environmental impact (SIDDALL et al, 1997;VITAL, 2008;BAYOUMY et al, 2008;MADI;UETA, 2009). Furthermore, this study evaluated the use of these parasites as environmental indicators for the effect of an impoundment (Jurumirim dam) on parasite communities, an approach that has not previously been reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was observed in the present study that the prevalence and mean abundance of total monogeneans and A. mizelli were significantly greater in the lentic stretch. This significant difference corroborates previous studies that reported the use of monogeneans as indicators of environmental impact (SIDDALL et al, 1997;VITAL, 2008;BAYOUMY et al, 2008;MADI;UETA, 2009). Furthermore, this study evaluated the use of these parasites as environmental indicators for the effect of an impoundment (Jurumirim dam) on parasite communities, an approach that has not previously been reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, these parasites are in direct contact with the environment (NACHEV, 2010) and are very sensitive to any change in water parameters (BAYOUMY et al, 2008). Therefore, studies on monogeneans as biomarkers have been conducted by taking different approaches: Siddall et al (1997) assessed the effects of exposure to relatively high concentrations of effluents from a pulp and paper mill on the prevalence, abundance and distribution of Dactylogyrus spp. on the gills of Rutilus rutilus that was sampled in Saravesi Lake, Finland.…”
Section: Discussionmentioning
confidence: 99%
“…Both increases and decreases in the prevalence of ectoparasitic monogeneans have been noted in fish exposed to various pollutants (Khan and Thulin 1991). In the present study area, we have shown experimentally an increase in Dactylogyrus species in the contaminated lake (Bagge and Valtonen 1996), but a decrease in the abundance of Dactylogyrus species communities when the BKME concentration was increased above that found in the lake (Siddal et al 1996). It seems, therefore, that the effluents influence the parasite communities both through the immunological response and condition of the host, although both affect also the parasites themselves.…”
Section: Fig 2 Effect Of Experimental Infection Bysupporting
confidence: 58%
“…As a consequence, the interspecific interaction between parasites remains a rare phenomenon (Cornell 1993;Gotelli and Rohde 2002). Indeed, the parasite communities observed in the Viaur River have low levels of species richness and relative abundances compared to other European rivers (Šimková et al 2001;Kadlec et al 2003), which may be related to the high level of eutrophication of the Viaur River (Guilmet 1997;Sidall et al 1997).…”
Section: Discussionmentioning
confidence: 99%